KAJIAN KESIAPAN GURU MATA PELAJARAN MATEMATIKA, BAHASA INDONESIA, DAN IPA SMP DALAM IMPLEMENTASI KURIKULUM 2013 DI KOTA SEMARANG - Isti Hidayah; Rahayu Pristiwati; Arif Widiyatmoko (Universitas Negeri Semarang, 2015)
The attainment of education in Indonesia is low. It can be seen from the measurement results of PISA 2013, which measures the ability of Mathematics, Reading, and Science for students in Junior High School education age. Meanwhile, in 2014 the implementation of Curriculum 2013 will be implemented 100% in class VII and VIII. How is the readiness of Junior High School teachers in Mathematics, Bahasa Indonesia, and Science regarding to the implementation of Curriculum 2013 in 2014? This study aimed to describe the understanding of junior high school teachers in Mathematics, Bahasa Indonesia, and Science to the 2013 curriculum, an innovative learning process, as well as authentic assessment in Semarang city. The study was designed as a descriptive study with a sample of teachers in Mathematics, Bahasa Indonesia, and Science (public and private) in the Semarang taken proportionally based on the accreditation status of A, B, and C. The statistical analysis that will be used is simple statistic equipped with the descriptive analysis of narrative. Research steps to be carried out are: sampling, research instruments development, data collection, data analysis, and results. The results indicated an understanding of 2013 curriculum by Junior High School teachers. It showed good result (score 3.7), understanding of the innovative learning process in using 2013 curriculum by Junior High School teachers showed good result (score 3.9), Junior High School teachers’ understanding of the authentic assessment showed considerable good result (score of 3.6), and Junior High School teachers in Bahasa Indonesia subjects, science and mathematics attitudes toward the implementation of curriculum 2013 showed good results. It can be seen from the average score of 3.8 with good categories on the questionnaire analysis. Most of teachers’ attitudes toward the implementation of 2013 curriculum indicated positive respond. On the other hand, factor of teacher readiness toward the implementation of 2013 curriculum still needs to be improved.Keywords: implementation of Curriculum 2013